Reconceptualizing Personality Disorders: An Eliminative Approach (Culturas Científicas, 2022)
Mental disorders can be used to justify medical, psychological, and judicial interventions. Besides enabling psychiatric reimbursements or public health programs and yielding social stereotypes. Nevertheless, the meaning of this concept has not ceased to arouse debate.I will argue that personality disorders as defined by DSM-5 fail to meet disease’s criteria according to the principal accounts (i.e. bio—statistical health theory, harmful disfunction, or disease entity) due to three independent reasons: (i) each individual disorder lacks clear dys/function candidates, and given the evolutionary psychology’ state of the art, it is unlikely that such candidates can be provided in the near future; (ii) the concept of harm (distress, impairment) applied to personality disorders is socially constituted (albeit not exclusively so), hence is more appropriate to talk about degrees of disability than individual disorders; and (iii) the lack of pathognomonic conditions for each disorder, alongside the high comorbidity and multimorbidity among personality disorders, hinders the current nosology and differential diagnostics validity.I will propose the elimination of personality disorders from psychiatric nosology as a solution. To eliminate personality disorders doesn’t imply disavowing the suffering of diagnosed individuals, nor ignoring that such suffering predates the diagnostic label (and will outlive it). Thus, a reconceptualization of such suffering in terms of disability, understood from the social model, will be proposed.
Keywords: Mental disorders; Harmful dysfunction; Pathognomonic conditions; Disability; Comorbidity